Exercise in the Female Life-Cycle in Britain, 1930-1970 - Macrae, Eilidh; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book examines how adolescence, menstruation and pregnancy were experienced or 'managed' by active women in Britain between 1930 and 1970, and how their athletic life-styles interacted with their working lives, marriage and motherhood. It explores the gendered barriers which have influenced women's sporting experiences. Women's lives have always been shaped by the socially and physically constructed life-cycle, and this is all the more apparent when we look at female exercise. Even self-proclaimed 'sporty' women have had to negotiate obstacles at various stages of their lives to try and maintain their athletic identity. So how did women overcome these obstacles to gain access to exercise in a time when the sportswoman was not an image society was wholly comfortable with? Oral history testimony and extensive archival research show how the physically and socially constructed female life-cycle shaped women's experiences of exercise and sport throughout these decades.
Chapter 1 - Introduction -- Chapter 2 - Physical Education Experiences -- Chapter 3 - Experiencing Exercise as a Young Woman -- Chapter 4 - Pregnancy, Menstruation and Active Women -- Chapter 5 - Exercise during Marriage and Motherhood -- Chapter 6 - Conclusion -- Appendix I -- Bibliography.
Keywords: Great Britain-History.; Gender Studies